2023
DOI: 10.1101/2023.03.17.23287040
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analyses of vaccine-specific circulating and bone marrow-resident B cell populations reveal benefit of delayed vaccine booster dosing with blood-stage malaria antigens

Abstract: We have previously reported primary endpoints of a clinical trial testing two vaccine platforms for delivery of Plasmodium vivax malaria DBPRII: viral vectors (ChAd63, MVA) and protein/adjuvant (PvDBPII with 50ug Matrix-M adjuvant). Delayed boosting was necessitated due to trial halts during the pandemic and provides an opportunity to investigate the impact of dosing regimens. Here, using flow cytometry - including agnostic definition of B cell populations with the clustering tool CITRUS - we report enhanced i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Indeed, the exploratory analyses of the PvDBPII-specific cellular responses conducted in the volunteers of this trial showed that memory B cells (CD19+ CD27+ IgG+) and plasma cells (CD19+ CD27+ CD38+) were significantly higher in delayed dosing regimens 7 days after final boost with both vaccine platforms used here (29). In addition, these two B cell populations are significantly correlated to PMR reduction (29). Extending the time between immunizations thus substantially improves antibody responses to PvDBPII potentially translating into greater efficacy.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Indeed, the exploratory analyses of the PvDBPII-specific cellular responses conducted in the volunteers of this trial showed that memory B cells (CD19+ CD27+ IgG+) and plasma cells (CD19+ CD27+ CD38+) were significantly higher in delayed dosing regimens 7 days after final boost with both vaccine platforms used here (29). In addition, these two B cell populations are significantly correlated to PMR reduction (29). Extending the time between immunizations thus substantially improves antibody responses to PvDBPII potentially translating into greater efficacy.…”
Section: Discussionmentioning
confidence: 90%
“…This improved immunogenicity in delayed dosing regimens may arise from increased B cell populations. Indeed, the exploratory analyses of the PvDBPII-specific cellular responses conducted in the volunteers of this trial showed that memory B cells (CD19+ CD27+ IgG+) and plasma cells (CD19+ CD27+ CD38+) were significantly higher in delayed dosing regimens 7 days after final boost with both vaccine platforms used here (29). In addition, these two B cell populations are significantly correlated to PMR reduction (29).…”
Section: Discussionmentioning
confidence: 90%